2000
DOI: 10.1002/1096-9101(2000)27:4<295::aid-lsm2>3.0.co;2-t
|View full text |Cite
|
Sign up to set email alerts
|

Linear lesions in myocardium created by Nd:YAG laser using diffusing optical fibers: In vitro and in vivo results

Abstract: Long linear lesions, necessary for duplication of the surgical maze procedure during catheter ablation of atrial fibrillation, may be created by using laser radiation delivered through flexible diffusing optical fiber tips. Further development of steerable catheters for endocardial atrial ablation and studies correlating thermal damage zones with electrophysiologic indicators of irreversible conduction block are warranted.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0
1

Year Published

2001
2001
2012
2012

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(15 citation statements)
references
References 32 publications
0
14
0
1
Order By: Relevance
“…For this particular reflector, the maximum intensity is achieved at a distance of 3.9 mm. This means that for AF operations, we can use a laser whose output power is eight times lower (10 W instead of 80 W) than demonstrated in recent studies related to side-emitting diffusers [17,18].…”
Section: Flexible Reflectormentioning
confidence: 95%
“…For this particular reflector, the maximum intensity is achieved at a distance of 3.9 mm. This means that for AF operations, we can use a laser whose output power is eight times lower (10 W instead of 80 W) than demonstrated in recent studies related to side-emitting diffusers [17,18].…”
Section: Flexible Reflectormentioning
confidence: 95%
“…In contrast, other studies have demonstrated transmural linear lesions in the canine with a 50‐W Nd‐YAG laser (1064 nm; “infrared”) without char formation or endocardial tissue disruption when applying lesions in a controlled setting. Additionally, further studies have shown that when there is inadequate contact, laser energy may generate more coagulum 24 …”
Section: Energy Sourcesmentioning
confidence: 99%
“…The ability of some laser (mostly infra‐red) ablation catheters to provide very good lesion depth control may make them superior to RF energy for ventricular arrhythmias. Multiple animal models clearly demonstrate the ability of laser to provide sharp deep myocardial lesions without endocardial disruption 22–24 . In humans, the use of laser for ventricular arrhythmias has been used more in the operating room during or following revascularization rather than percutaneously 20 .…”
Section: Arrhythmia‐specific Therapiesmentioning
confidence: 99%
See 1 more Smart Citation
“…The utilization of laser in the treatment of AF is recent with, until now, only experimental studies. Fried et al [24] conducted an experimental study using the Nd:YAG LASER system through optical fibers. The authors reported transmural lesions without evidence of tissue perforation or of lesions of adjacent structures.…”
Section: Laser Raysmentioning
confidence: 99%